Infantile GM1 Gangliosidosis Presenting with Neuroregression and Leukodystrophy: A Case Report - Khairunnisa Mohd Ansari; Noor Azlin Azraini Che Soh; Noor Hafidah Hamran; Bin Alwi Zilfalil; Julaina Abdul Jalil; Ahmad Shahir Mohamad Nazri; Noor Mohd Firdaus Othman (Malaysian Journal of Paediatrics and Child Health, 2026)
GM1 gangliosidosis is a rare autosomal recessive lysosomal storage disorder caused by β-galactosidase deficiency, resulting in GM1 ganglioside accumulation. The infantile form presents early with developmental regression and hypotonia. We report a 20-month-old Malay girl with progressive neuroregression, macrocephaly, myoclonic jerks, hypotonia, bilateral cherry-red maculae, frontal prominence, narrow bifrontal diameter, short neck, epicanthic folds, flat nasal bridge, tented upper lips, downturned mouth, high-arched palate, widely spaced nipples, and relatively short limbs. Brain MRI revealed cerebral atrophy with leukodystrophy; EEG demonstrated occasional sharp wave discharges over the right frontal and left parietal regions. Urine oligosaccharide analysis, lysosomal enzyme assay, and molecular genetic findings, interpreted together with the clinical presentation, supported the diagnosis of infantile GM1 gangliosidosis. This case underscores the importance of early recognition and the diagnostic value of enzyme and molecular genetics studies.